2022
DOI: 10.1186/s40850-022-00126-9
|View full text |Cite
|
Sign up to set email alerts
|

Personality matters: exploring the relationship between personality and stress physiology in captive African lions

Abstract: Background Considering animals as individuals and not as species is becoming increasingly essential to animal welfare management in captive settings. Recent studies on big cat personalities and coping strategies suggest personality can help big cats cope in their surroundings. Yet a large portion of the published literature focuses on understanding either the personality or stress physiology of big cats. Our research shows how integrating an improved understanding of the personality of big cats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…Age was not considered (e.g. Bartolomé et al 2013;Vaz et al 2022), since in the field squirrels can be classified just as young, subadult, or adult; only adults were part of the study. Ambient temperature and humidity were provided by the weather station located in Greer (AZ, USA; 2622 m a.s.l., 11 km from the study area; https://www.wunderground.com/) that records data every 4 min.…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Age was not considered (e.g. Bartolomé et al 2013;Vaz et al 2022), since in the field squirrels can be classified just as young, subadult, or adult; only adults were part of the study. Ambient temperature and humidity were provided by the weather station located in Greer (AZ, USA; 2622 m a.s.l., 11 km from the study area; https://www.wunderground.com/) that records data every 4 min.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Several studies investigating stress response in domestic or laboratory animals recorded the basal temperature of each individual and successfully studied the changes in body temperature from a neutral to a stressed state (Cabanac & Briese 1992;Lee et al 2000;Kramer et al 2004;Lowe et al 2005). Eye temperature of African lions (Panthera leo) in a neutral state, that is, basal core temperature, measured by IRT did not vary with personality (Vaz et al 2022). A major challenge in studies investigating basal core temperature in wild animals is that trapping and handling the animal are stressful events in their own right, and the body temperature measured (either with IRT or thermometers) is already affected by the physiological stress reaction of the animal mediated by its personality.…”
Section: Personality and Physiological Response To Acute Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…[49] concluded some individual may approach or respond more to novel objects that other individual. Individual personality matters already published on lion [50].…”
Section: 3mentioning
confidence: 99%
“…The authors attributed the absence of any ocular thermal response to a potentially enjoyable emotional state, suggesting that IRT could be useful for identifying emotional states in animals [44]. Vaz et al [45] found a similar response in African lions (P. leo), where the IRT response at the ocular level was used to understand large felines' personality and stress physiology, when coordinated with ethological studies and fecal glucocorticoid levels. The authors identified three personality types by studying 22 African lions in two locations, (dominant, gentle, and neurotic).…”
Section: Ocular Window (Regio Ocularis)mentioning
confidence: 99%